Kedudukan Hukum Uang Panai’ dalam Perkawinan Masyarakat Bugis-Makassar - Wiwin, Wiwin; Saharuddin, Saharuddin (Jurnal Litigasi Amsir, 2025)
Indonesia, as a multicultural country, possesses diverse traditions, including those related to marriage. In the Bugis-Makassar society, uang panai’ is a deeply rooted tradition that serves as an integral part of marriage, symbolizing respect for women and the responsibility of the groom. Despite its profound philosophical meaning, the practice of uang panai’ has undergone a shift in meaning, often becoming a status symbol, which has led to delays or even cancellations of marriages. This study aims to examine the legal status of uang panai’ in the Indonesian legal system and its role within Bugis-Makassar society. This research employs a normative legal research method, focusing on a statutory approach, a conceptual approach, and an Islamic legal approach. The findings indicate that uang panai’ is classified as customary law, which is recognized within Indonesia’s legal framework. Its legal status can be found in Fatwa MUI Sulsel No. 2 of 2022 on Uang Panai’, although this fatwa does not carry binding legal authority as legislation. Within Bugis-Makassar society, uang panai’ functions as a customary norm with moral binding force; however, its implementation must be proportional to ensure it does not become an excessive burden on the groom and his family.